Logistic Regression Analysis of Mode of Delivery Influencing Nutritional Status among Under-Five Children in Bangladesh: Survey in Rural Area of Rajshahi District - Hossain, Md Aslam; Karim, Md Reazul; Md Al Mamun, Abu Sayed; Islam, Md Saimul; Hossain, Md Golam (International Journal of Statistical Sciences, 2023)
Caesarean delivery is a surgical procedure in which a fetus is delivered through an incision in the mother's abdomen and uterus. If there are no complications with women pregnancy or labor, a vaginal birth is safer than a caesarean birth. Worldwide the rates of C-section have gradually increased in the latest decades. The aim of the study was to determine the prevalence of caesarian delivery, and to investigate the impact of caesarian delivery on nutritional status of under-five children in the rural area of Rajshahi district, Bangladesh. This was a cross sectional study. Data was collected from Rajshahi district using multistage sampling. A total number of 540 mothers having at least one under-five children currently living together were considered. In order to data analysis, descriptive statistics, Z-proportional test and both univariable and multivariable logistic regression models were in this study according to our objectives. This study revealed that the prevalence of caesarian delivery among mothers living in the rural area of Rajshahi, Bangladesh was 34.4%. The prevalence of stunting, underweight and wasting among under-five children were 43.70%, 39.63% and 27.96% respectively. The stunting, underweight and wasting under-five children were 32.6%, 28.0% and 29.1% respectively who were born by caesarian delivery, these were significantly (p<0.01) lower compared to children who were born by vaginal delivery. However, the logistic model demonstrated that children who were born by vaginal delivery were more likely to have underweight [COR= 1.617; 95%CI: 1.114-2.347; p<0.05] compared to children who were born by caesarian delivery. After controlled the effect of other independent variables such as mothers’ age, education, occupation, nutritional status, fathers, education, occupation, number of family members, type of family and social class, found that children who were born by vaginal delivery had a 1.589-fold higher chance to have underweight compared to children who were born by caesarian delivery [AOR= 1.589; 95%CI: 1.063-2.377; p<0.05]. This study found the high prevalence in stunting, underweight and wasting among under-five children in the rural area of Bangladesh. Bangladesh government and other non-government organizations should take special attention to overcome the problem. International Journal of Statistical Sciences, Vol. 23(2), November, 2023, pp 107-116